PLUSRonda Assist Mobile Application (PAMA) using GPS for automatic incident location detection / Mohammad Nadzrin Mohd Nasri - Mohd Nasri, Mohammad Nadzrin (2017)
Projek Lebuhraya Usahasama Berhad (PLUS BERHAD) is the biggest highway operator in Malaysia that where responsible in the operation, maintenance and facilities management along the 772 km PLUS expressways. Whenever a user of the PLUS expressway is in need of help due to car failure or accident, they will only have option to either call the PLUS hotline or walk to the nearest emergency phone available on the side of the expressway to get help from PLUSRonda. PLUS Malaysia Berhad also introduces ‘PLUS Mobile App’, a mobile application that enables the expressway user to know about the latest highway traffic information. The idea to develop a PLUSRonda assist mobile application using GPS for automatic incident location detection, this mobile application will alert the nearest PLUSRonda around and send notification to get assistance from PLUSRonda directly and efficiently. The findings and analysis of the work was carried out and an interview was done to ensure that the objective and user requirement is met. For the future work, this application can be improved by adding a few more functions to this mobile application. Such as, adding a function where the user can know nearest workshop and user can send location without internet connection. The mobile application also will do better in the future.